Strategi Pengembangan Wisata Pantai Are Guling sebagai Daya Tarik Wisata di Kabupaten Lombok Tengah Nusa Tenggara Barat - Yudha Adytya Pertywy; Hamdani Satriawan (Lembaga Yasin AlSys, 2026)
The development of Are Guling Beach as a tourist attraction in Central Lombok Regency still faces several problems, particularly limited accessibility, inadequate facilities, and suboptimal management. This study aimed to formulate effective development strategies based on internal and external factors that influence the Are Guling Beach tourism area. This study used a qualitative descriptive approach. Data were collected through observation, interviews, questionnaires, and documentation, and were then analyzed using the SWOT method. The results showed that Are Guling Beach has strong natural potential, good community support, and an increasing trend of tourist visits, particularly domestic tourists. However, its development is still constrained by poor road access, limited facilities, and weak organizational management. Development opportunities are supported by relevant regulations and increasing interest in tourism, whereas threats arise from competition with other destinations, including the Mandalika Special Economic Zone. The formulated development strategies include improving accessibility, enhancing facilities, strengthening human resources, and optimizing promotion. The conclusion of this study confirms that the development of Are Guling Beach requires integrated management among the government, the community, and the private sector to optimize the existing tourism potential. The implications of this study emphasize the importance of sustainable tourism planning, infrastructure strengthening, and human resource capacity building to improve destination competitiveness and expand the reach of tourist visits.